Mekanisme dan Implementasi Fraud Control Plan: Studi Kasus pada Rumah Sakit Umum Daerah - Alharis Tagora; Vima Tista Putriana (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2022)
Fraud can take different forms, one of them is known as ‘corruption’. Corruption is still high in Indonesia up until now. This indicates that repressive strategies should be accompanied by preventive strategies in tackiling fraud. Badan Pengawasan Keuangan dan Pembangunan, in its role as an internal auditor of the government has attempted to develop ‘Fraud Control Plan’ (FCP). FCP has ten attributes: anti-fraud policies, accountability structures, standards of behavior and discipline, fraud risk management, employee awareness, fraud reporting system, whistleblower protection, customer and community awareness, investigative procedures, and disclosure to external parties. This study aims to explore and understand the fraud control mechanism and how it has been implemented in local hospital XYZ and to assess the level of consistency of the existing fraud control mechanism with the ten FCP attributes. The research was designed as a qualitative research, with data collection methods involved interviews and documentary analysis. The results showed that local hospital XYZ already has a fraud control mechanism in place at the moment: the local hospital has formed a team in charge of fraud handling and an anti-fraud policy has been formulated. However, the mechanism has not meet the ten FCP attributes yet.